Sperm blocking is not a male adaptation to sperm competition in a parasitoid wasp. (8th December 2017) - Boulton, Rebecca A; Cook, Nicola; Green, Jade; (Ginny) Greenway, Elisabeth V; Shuker, David M
Abstract : Although mating with multiple males should provide females with more sperm, in the parasitoid wasp Nasonia vitripennis females that mate multiply produce more unfertilized eggs (which in this species develop as sons due to haplodiploidy). We tested whether this was due to males "blocking" or "incapacitating" the sperms of their rivals. Instead of being a male adaptation to sperm competition, however, our results suggest that this reflects a female constraint on sperm processing. Abstract: The extent to which sperm or ejaculate-derived products from different males interact during sperm competition—from kamikaze sperm to sperm incapacitation—remains controversial. Repeated matings in the parasitoid wasp Nasonia vitripennis lead to a short-term reduction of efficient sperm use by females, which is crucial for a haplodiploid organism when needing to allocate sex adaptively (i.e. by fertilizing eggs to produce daughters). Repeated matings by females in this species, therefore, constrain sex allocation through this "sperm-blocking" effect, eliciting a cost to polyandry. Here, we explore the causes and consequences of sperm blocking and test the hypothesis that it is an ejaculate-related trait associated with sperm competition. First, we show that sperm blocking, which leads to an overproduction of sons, is not correlated with success in either offensive or defensive roles in sperm competition. Then, we show that the extent of sperm blocking is not affected by self–self or kin–kin ejaculate interactions when compared to self vs nonself or kin versus nonkin sperm competition. Our results suggest that sperm blocking is not a sperm competition adaptation, but is instead associated with the mechanics of processing sperm in this species, which are likely shaped by selection on female reproductive morphology for adaptive sex allocation.